2010
DOI: 10.1051/0004-6361/201014523
|View full text |Cite
|
Sign up to set email alerts
|

Strong absorption by interstellar hydrogen fluoride:Herschel/HIFI observations of the sight-line to G10.6–0.4 (W31C)

Abstract: We report the detection of strong absorption by interstellar hydrogen fluoride along the sight-line to the submillimeter continuum source G10.6-0.4 (W31C). We have used Herschel's HIFI instrument, in dual beam switch mode, to observe the 1232.4763 GHz J = 1−0 HF transition in the upper sideband of the Band 5a receiver. The resultant spectrum shows weak HF emission from G10.6-0.4 at LSR velocities in the range -10 to -3 km s −1 , accompanied by strong absorption by foreground material at LSR velocities in the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 16 publications
4
63
1
Order By: Relevance
“…The OH + ground state lines are known with a good accuracy of ∼1.5 MHz. Velocities obtained by the empirical model agree well with the velocities where deep HCO + (1-0) (Keene et al 1999;Godard et al 2010), p-H 2 O and HF (Neufeld et al 2010) and HI Fish et al (2003) absorptions are detected. It is remarkable that one of the strongest OH + absorption features at V LSR ∼ 7 km s −1 coincides with a strong dip in the HI profile that has no counterpart in CO emission Falgarone et al (2005).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The OH + ground state lines are known with a good accuracy of ∼1.5 MHz. Velocities obtained by the empirical model agree well with the velocities where deep HCO + (1-0) (Keene et al 1999;Godard et al 2010), p-H 2 O and HF (Neufeld et al 2010) and HI Fish et al (2003) absorptions are detected. It is remarkable that one of the strongest OH + absorption features at V LSR ∼ 7 km s −1 coincides with a strong dip in the HI profile that has no counterpart in CO emission Falgarone et al (2005).…”
Section: Resultssupporting
confidence: 75%
“…The molecular cloud surrounding the star-forming complex shows evidence of continuing accretion onto the embedded stars (Keto & Wood 2006;Sollins & Ho 2005). As discussed by Neufeld et al (2010), line absorption by foreground gas has been detected from [OI] (Keene et al 1999), 13 CH + (Falgarone et al 2005), HCO + , HCN, HNC, CN (Godard et al 2010), and atomic hydrogen (Fish et al 2003). While the gas associated directly with G10.6−0.4 is detected in the velocity range −5 to +5 km s −1 , the A&A 518, L110 (2010) foreground gas along the line of sight is confined to the velocity interval from ∼5 to 45 km s −1 .…”
Section: Introductionmentioning
confidence: 92%
“…Monje et al (2014) reported observations of HF in two luminous galaxies, NGC 253 and NGC 4945, using the Heterodyne Instrument for the Far-Infrared (HIFI) on the Herschel Space Observatory. With Herschel/HIFI, Neufeld et al (2010) detected HF in absorption from the ground rovibrational state. Phillips et al (2010) presented a detection of the fundamental rotational transition of hydrogen fluoride in absorption toward Orion KL using Herschel/HIFI.…”
Section: Introductionmentioning
confidence: 99%
“…Relative abundances measured in diffuse clouds show that, indeed, fluorine is essentially locked in HF (e.g., Neufeld et al 2010;Monje et al 2011), whereas HCl accounts for less than 1% of the elemental chlorine due to a rich chemistry initiated by ionizing radiation (e.g., Monje et al 2013). In dense molecular clouds, HF and HCl are found to be strongly depleted, which is thought to be the result of nearly all HF and HCl molecules freezing out onto grains in such cold environments (Peng et al 2010;Emprechtinger et al 2012).…”
Section: Introductionmentioning
confidence: 99%